Characterization of the novel HLA‐C*16:173 allele by sequencing‐based typing. (19th October 2020) - Elsermans, Vincent; Visentin, Jonathan; Top, Isabelle; Varlet, Pauline; Labalette, Myriam
Abstract : HLA‐C*16:173 differs from HLA‐C*16:01:01:01 by one nucleotide substitution in codon 36 in exon 2.